Copper‐Enriched Prussian Blue Nanomedicine for In Situ Disulfiram Toxification and Photothermal Antitumor Amplification. Issue 17 (12th March 2020) - Wu, Wencheng; Yu, Luodan; Pu, Yinying; Yao, Heliang; Chen, Yu; Shi, Jianlin
Abstract: In situ toxification of less toxic substance for the generation of effective anticarcinogens at the specific tumor tissue has been a novel paradigm for combating cancer. Significant efforts have been recently dedicated to turning clinical‐approved drugs into anticancer agents in specific tumor microenvironment by chemical reactions. Herein, a hollow mesoporous Prussian blue (HMPB)‐based therapeutic nanoplatform, denoted as DSF@PVP/Cu‐HMPB, is constructed by encapsulating alcohol‐abuse drug disulfiram (DSF) into the copper‐enriched and polyvinylpyrrolidone (PVP)‐decorated HMPB nanoparticles to achieve in situ chemical reaction‐activated and hyperthermia‐amplified chemotherapy of DSF. Upon tumor accumulation of DSF@PVP/Cu‐HMPB, the endogenous mild acidity in tumor condition triggers the biodegradation of the HMPB nanoparticle and the concurrent co‐releases of DSF and Cu 2+, thus forming cytotoxic bis( N, N ‐diethyl dithiocarbamato)copper(II) complexes (CuL2 ) via DSF‐Cu 2+ chelating reaction. Moreover, by the intrinsic photothermal‐conversion effect of PVP/Cu‐HMPBs, the anticancer effect of DSF is augmented by the hyperthermia generated upon near‐infrared irradiation, thus inducing remarkable cell apoptosis in vitro and tumor elimination in vivo on both subcutaneous and orthotopic tumor‐bearing models. This strategy of in situ drug transition by chemical chelation reaction and photothermal‐augmentation provides a promising paradigm for designing novel cancer‐therapeutic nanoplatforms. Abstract : This work provides an intriguing paradigm of in situ conversion of disulfiram into an effective anticarcinogen combined with therapeutic efficacy amplification for tumor eradication and excellent biosafety, which is also expected to contribute to the future design of novel in situ‐activated and external‐stimulus‐augmented therapeutic nanoplatforms.